2011
DOI: 10.1007/s10339-011-0431-y
|View full text |Cite
|
Sign up to set email alerts
|

Gestalt compositionality and instruction-based meaning construction

Abstract: We would like to propose a new model of meaning construction based on language comprehension considered as a dynamic process during which the meaning of each linguistic unit and the global meaning of the sentence are determined simultaneously. This model, which may be called "gestalt compositionality," is radically opposed to the classic compositional mechanism advocated by linguistic formalism based on the primacy of syntax. The process considers the syntactic structure of an utterance as the product of meani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
(22 reference statements)
0
13
0
2
Order By: Relevance
“…letters, squares etc. ), visual discrimination is hindered, but simple target detection is facilitated or not affected at all by visual simulations (e.g., [7], [18]). This dissociation between the findings in discrimination and detection tasks might be due to the fact that visual discrimination and detection tasks differ in various aspects, such as the demands for visual processing resources, response selection demands and also, the time course of processing [38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…letters, squares etc. ), visual discrimination is hindered, but simple target detection is facilitated or not affected at all by visual simulations (e.g., [7], [18]). This dissociation between the findings in discrimination and detection tasks might be due to the fact that visual discrimination and detection tasks differ in various aspects, such as the demands for visual processing resources, response selection demands and also, the time course of processing [38].…”
Section: Discussionmentioning
confidence: 99%
“…In paradigms implementing attentional cueing tasks, it has been suggested that words result in automatic shifts of attention. These inferences were drawn from both facilitation and inhibition effects (e.g., [14], [7]). These attentional shifts might also underlie the reported facilitation of saccadic eye movements towards compatible locations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So as to account for the various uses associated with syntactic patterns and categories, and the extremely large (or maybe unlimited) number of possible interactions of the unit with its co-text, Col et al (2012) suggests a model based on a gestalt compositionnal approach. We consider that the meaning of an utterance is constructed in the course of a double, dynamic process leading to a temporary, tentative semantic balance between the different interactions.…”
Section: Version De Travail (Non Définitive)mentioning
confidence: 99%
“…This capacity of convocation-evocation is what defines a linguistic unit; it is not its "meaning" per se but what we call its "instruction". As an example, the instruction supplied by "over" will be the following one (Col 2012 and:…”
Section: Version De Travail (Non Définitive)mentioning
confidence: 99%